2020
DOI: 10.48550/arxiv.2009.04262
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Towards optimization techniques on diffeological spaces by generalizing Riemannian concepts

Abstract: Diffeological spaces firstly introduced by J.M. Souriau in the 1980s are a natural generalization of smooth manifolds. However, optimization techniques are only known on manifolds so far. Generalizing these techniques to diffeological spaces is very challenging because of several reasons. One of the main reasons is that there are various definitions of tangent spaces which do not coincide. Additionally, one needs to deal with a generalization of a Riemannian space in order to define gradients which are indispe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…This was performed in [9] via mild considerations on colimits in categories. From another viewpoint, the external tangent space is spanned by derivations, and one can define the cone of derivations which are defined by germs of paths [32] as well as its vector space completion in the space of derivations following [18]. For finite dimensional manifolds these tangent spaces coincide.…”
Section: 5mentioning
confidence: 99%
“…This was performed in [9] via mild considerations on colimits in categories. From another viewpoint, the external tangent space is spanned by derivations, and one can define the cone of derivations which are defined by germs of paths [32] as well as its vector space completion in the space of derivations following [18]. For finite dimensional manifolds these tangent spaces coincide.…”
Section: 5mentioning
confidence: 99%
“…Metrics for diffeological spaces have been researched to a lesser extent. However, most concepts can be transferred and in [66] a Riemannian metric is defined for a diffeological space, which yields a Riemannian diffeological space. Additionally, the Riemannian gradient and a steepest descent method on diffeological spaces are defined, assuming a Riemannian metric is available.…”
Section: Examplementioning
confidence: 99%
“…Therefore, the main objective for formulating optimization algorithms on a shape space, i.e., the generalization of concepts such as the definition of a gradient, a distance measure and optimality conditions, is not yet reached for the novel space B 1 2 (Γ 0 ). However, the necessary objects for the steepest descent method on a diffeological space are established and the corresponding algorithm is formulated in [66]. It is nevertheless worth mentioning that various numerical experiments, e.g., [31,[91][92][93], have shown that shape updates obtained from the Steklov-Poincaré metric can also be applied to problems involving non-smooth shapes.…”
Section: The Shape Space Bmentioning
confidence: 99%
See 1 more Smart Citation